Scavenging organic nitrogen and remodelling lipid metabolism are key survival strategies adopted by the endophytic fungi, Serendipita vermifera and Serendipita bescii to alleviate nitrogen and phosphorous starvation in vitro. Issue 4 (1st May 2019) - Ray, Prasun; Abraham, Paul E.; Guo, Yingqing; Giannone, Richard J.; Engle, Nancy L.; Yang, Zamin K.; Jacobson, Daniel; Hettich, Robert L.; Tschaplinski, Timothy J.; Craven, Kelly D.
Summary: Serendipitaceae represents a diverse fungal group in the Basidiomycota that includes endophytes and lineages that repeatedly evolved ericoid, orchid and ectomycorrhizal lifestyle. Plants rely upon both nitrogen and phosphorous, for essential growth processes, and are often provided by mycorrhizal fungi. In this study, we investigated the cellular proteome of Serendipita vermifera MAFF305830 and closely related Serendipita vermifera subsp. bescii NFPB0129 grown in vitro under (N) ammonium and (P) phosphate starvation conditions. Mycelial growth pattern was documented under these conditions to correlate growth‐specific responses to nutrient starvation. We found that N‐starvation accelerated hyphal radial growth, whereas P‐starvation accelerated hyphal branching. Additionally, P‐starvation triggers an integrated starvation response leading to remodelling of lipid metabolism. Higher abundance of an ammonium transporter known to serve as both an ammonium sensor and stimulator of hyphal growth was detected under N‐starvation. Additionally, N‐starvation led to strong up‐regulation of nitrate, amino acid, peptide, and urea transporters, along with several proteins predicted to have peptidase activity. Taken together, our finding suggests S. bescii and S. vermifera have the metabolic capacity for nitrogen assimilation from organic forms of N compounds. We hypothesize that the nitrogen metabolite repression is a key regulator of such organic N assimilation.